Створення Української академії наук у Києві в 1918 р.: хронологія подій - Дороніна, Г.А.; Луговський, О.Г.; Мушкало, Ю.І.; Храмов, Ю.О. (Наука та наукознавство, 2018)
У статті висвітлено передісторію створення Української академії наук (УАН), зокрема діяльність Наукового товариства ім. Т. Шевченка та Українського наукового товариства як попередників УАН, докладну хронологію подій, пов’язаних зі створенням, на думку М.С. Грушевського, УАН у Києві протягом 1918 року, на тлі зміни політичної влади в той період — від Української Народної Республіки до Гетьманату і Директорії, аж до приходу більшовиків. В статье освещена предыстория создания Украинской академии наук (УАН) в конце 80-х — начале 90-х годов XIX века, в частности деятельность Научного общества им. Т. Шев ченко и Украинского научного общества как предшественников, по мнению М.С. Грушевского, УАН. Представлена подробная хронология событий, связанных с созданием УАН в Киеве на протяжении 1918 года, на фоне изменения политической власти в тот период — от Украинской Народной Республики до Гетьманата и Директории, вплоть до прихода большевиков. A ramified system of higher education establishments existed in Ukraine in late 19 — early 20 century, with some portions of research performed in humanitarian, natural and technical fields. This gives grounds to say that the conditions for creating the Academy of Sciences as an entity bringing together outstanding scientists on radically new principles but with government support and organizing an extensive network of research in diversified fields existed at early 20 century. A favorable background for creating the Ukrainian Academy existed in the Western Ukraine. An attempt to establish it was made in the city of Lviv in 1873 by creating T. Shevchenko Scientific Socie ty with the mission of promoting the Ukrainian letters. The Ukrainian Scientific Society was created in 1907 in Kyiv, which members were best representatives of the Ukrainian intel lec tual elite.